Pengaruh Interaksi Sosial Terhadap Keterampilan Bermasyarakat Mahasiswa KKN Universitas Negeri Padang Periode Januari-Juni 2023 - Mai Sri Lena; Hana Shilfia Iraqi; Muhammad Fauzan; Aditya Febriansyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Community skills are needed for every individual, not covering any age for both students and the general public, as for Kuliah Kerja Nyata (KKN), namely Community Empowerment Learning-based activities carried out by students. This research focuses on the impact of real work lectures on students' social skills. This research is a type of research that is a quantitative descriptive research. Data collection was obtained through filling out a list of questions (questionnaire) using the Google form. Data analysis using descriptive statistical analysis. The author found that targeted students improved their social skills, both in relation to the surrounding community and in relation to group relationships. The conclusion from the results of the tests carried out is that the implementation of work lectures has an influence on the development of students' social skills.